Therapeutic Effects of Systemic Vitamin K2 and Vitamin D3 on Gingival Inflammation and Alveolar Bone in Rats With Experimentally Induced Periodontitis. Issue 5 (1st May 2015) - Aral, Kübra; Alkan, Banu Arzu; Saraymen, Recep; Yay, Arzu; Şen, Ahmet; Önder, Gözde Özge
Abstract : Background: The synergistic effects of vitamin D3 and vitamin K2 on bone loss prevention have been reported. This study evaluates the effects of vitamin D3 and vitamin K2 supplementation in conjunction with conventional periodontal therapy (scaling and root planing [SRP]) on gingival interleukin (IL)‐1β and IL‐10, serum bone alkaline phosphatase (B‐ALP) and tartrate‐resistant acid phosphatase 5b (TRAP‐5b), and calcium and alveolar bone levels in rats with experimentally induced periodontitis. Methods: Seventy‐two rats were divided into the following groups: 1) healthy; 2) periodontitis; 3) SRP; 4) SRP + vitamin D3; 5) SRP + vitamin K2; and 6) SRP + vitamins K2 and D3. Periodontitis was induced by ligature placement for 7 days, and vitamin K2 (30 mg/kg) and/or vitamin D3 (2 μg/kg) were administered for 10 days in the SRP + vitamin D3, SRP + vitamin K2, and SRP + vitamins K2 and D3 groups by oral gavage. On day 18, the animals were sacrificed, serum B‐ALP, TRAP‐5b, and calcium levels were measured, gingiva specimens were extracted for IL‐1β and IL‐10 analysis, and distances between the cemento‐enamel junction and alveolar bone crest were evaluated. Results: Alveolar bone levels in the periodontitis group were significantly greater than those in the other five groups. No significant differences were found in gingival IL‐1β and IL‐10, serum B‐ALP and TRAP‐5b, and calcium and alveolar bone levels between the groups receiving SRP and vitamins and the group receiving SRP alone. Conclusion: Within the limitations of this study, vitamin D3 and K2 alone or in combination did not affect gingival IL‐1β and IL‐10, serum B‐ALP and TRAP‐5b levels, or alveolar bone compared with conventional periodontal therapy alone.